2020
DOI: 10.1038/s41598-020-78502-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell–cell fusion of mesenchymal cells with distinct differentiations triggers genomic and transcriptomic remodelling toward tumour aggressiveness

Abstract: Cell–cell fusion is a physiological process that is hijacked during oncogenesis and promotes tumour evolution. The main known impact of cell fusion is to promote the formation of metastatic hybrid cells following fusion between mobile leucocytes and proliferating tumour cells. We show here that cell fusion between immortalized myoblasts and transformed fibroblasts, through genomic instability and expression of a specific transcriptomic profile, leads to emergence of hybrid cells acquiring dissemination propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(74 reference statements)
3
10
0
Order By: Relevance
“…Likewise, a substantial shift in the phenotypes of MDA-MB-231 × SUM159PT hybrids at early (2) and extended (10) passages was observed, which was further consistent with the selection of a fit subpopulation of hybrid cells and additional diversification [16]. Hybrid clones derived from human breast epithelial cells and human breast cancer cells possessed a unique mean chromosomal number [64,113], which is in accordance with recent data of Delespaul et al and Lartigue and colleagues who also showed that mesenchymal tumor hybrid clones exhibited a unique chromosomal content [114][115][116]. In this connection, it should be kept in mind that PSHP/AKE does not stop at a certain time point, e.g., after 10 or 15 divisions.…”
Section: Post-fusion Processessupporting
confidence: 89%
“…Likewise, a substantial shift in the phenotypes of MDA-MB-231 × SUM159PT hybrids at early (2) and extended (10) passages was observed, which was further consistent with the selection of a fit subpopulation of hybrid cells and additional diversification [16]. Hybrid clones derived from human breast epithelial cells and human breast cancer cells possessed a unique mean chromosomal number [64,113], which is in accordance with recent data of Delespaul et al and Lartigue and colleagues who also showed that mesenchymal tumor hybrid clones exhibited a unique chromosomal content [114][115][116]. In this connection, it should be kept in mind that PSHP/AKE does not stop at a certain time point, e.g., after 10 or 15 divisions.…”
Section: Post-fusion Processessupporting
confidence: 89%
“…Similar findings were reported for hybrid cells that were derived from immortalized myoblasts and transformed fibroblasts by exhibiting clonogenic ability and dissemination properties [31]. Moreover, hybrid tumors were found to mimic the histological characteristics of undifferentiated pleomorphic sarcomas with incomplete muscular differentiation, suggesting that cell fusion might favor specific sarcoma development according to the differentiation lineage of parent cells [31].…”
Section: Evidence For Cancer Cell Fusion By In Vitro Studiessupporting
confidence: 76%
“…Several studies using genetically modified cancer cells and transgenic mouse models have revealed cancer cell fusion among themselves (homotypic fusion) or with other cell types in the tumor microenvironment, such as macrophages, CAFs, or MSC (heterotypic fusion) [31,32,73,123,125,198,[204][205][206].…”
Section: Evidence For Cancer Cell Fusion By In Vitro Studiesmentioning
confidence: 99%
See 2 more Smart Citations